Effective teacher hiring : a guide to getting the best - Peterson, Kenneth D. (Association for Supervision and Curriculum Development, 2002)
Because student learning depends on quality instructors, teacher hiring is perhaps the single most important issue facing schools today. In Effective Teacher Hiring: A Guide to Getting the Best, Kenneth D. Peterson presents an innovative, multi-tiered framework for teacher selection. The program is sufficiently flexible to use in school systems large or small, but designed rigorously enough to provide for checks and balances at every turn, guarantee a voice in the process for students and parents, and ensure that only the best available candidates are ultimately chosen. In addition to step-by-step instructions for implementing the hiring program, Effective Teacher Hiring offers . Lists of hiring dos and don'ts . Resume and portfolio assessment strategies . Sample recruitment flyers, contracts, and interview questions . A rundown of legal issues related to hiring We must ensure that our students have the best available teachers--and to get the best, we must first learn how best to hire. This book is an invaluable resource for educators committed to providing the best possible instruction to their students.